Christina Rossetti's Feminist Theology - Palazzo, L. author. aut Link
XIV, 165 p.
Keywords: This volume disputes the assumption that Rossetti was a follower of Keble and Pusey, and shows how her dissatisfaction with the male-dominated call to celibacy led her to reject their notions of worldliness, and to form a closer bond with the physical world and the body.